Visions of the future - a socialist departure from gloom? - Paul Robert Auerbach; Peter Skott (University of Massachusetts, Department of Economics, 2021)
A vision of universalised human freedom, equality, security and democracy emerged in the wake of the Scientific Revolution and the Enlightenment, the British Industrial Revolution and the French Revolution. This vision, not even approximately practicable at the time, is now well within reach. A viable socialist strategy will not be oriented around an encompassing central plan, but rather an agenda of human-centred goals - the creation of preconditions for all individuals to fully realise their personal capacities and to function as free citizens, exercising control individually and collectively, at the workplace and in society. Central to the realisation of such a programme will be a focus on the crucial role played by the first years of life in shaping human development and in the formation of class hierarchies.
Keywords: B51; H40; P16; 330; Phillips curve; underemployment; distributional conáict; structuralist model; Sozialismus; Zukunft; Entwicklung